Role of Sphingosine Kinase in Type 2 Diabetes Mellitus - Qi, Yanfei; Wang, Wei; Song, Ziyu; Aji, Gulibositan; Liu, Xin Tracy; Xia, Pu (Frontiers in Endocrinology, 2021)
Sphingolipids are a class of essential lipids, functioning as both cell membrane constituents and signaling messengers. In the sphingolipid metabolic network, ceramides serve as the central hub that is hydrolyzed to sphingosine, followed by phosphorylation to sphingosine 1-phosphate (S1P) by sphingosine kinase (SphK). SphK is regarded as a "switch" of the sphingolipid rheostat, as it catalyzes the conversion of ceramide/sphingosine to S1P, which often exhibit opposing biological roles in the cell. Besides, SphK is an important signaling enzyme that has been implicated in the regulation of a wide variety of biological functions. In recent years, an increasing body of evidence has suggested a critical role of SphK in type 2 diabetes mellitus (T2D), although a certain level of controversy remains. Herein, we review recent findings related to SphK in the field ofT2D research with a focus on peripheral insulin resistance and pancreatic β-cell failure. It is expected that a comprehensive understanding of the role of SphK and the associated sphingolipids in T2D will help to identify druggable targets for future anti-diabetes therapy.